EU's Educational Policy and Norm-Building in Candidate Countries: The Case of Erasmus+ in Turkey (Global Journal of Human-Social Science, 2020)
This article analyzes the impact of the EU's educational policy on the construction of European norms and identity in candidate countries. One significant tool of educational policy in this respect is the exchange programs, which are now combined under the single framework of Erasmus+ and in order the determine the relationship between educational policy and normbuilding, the article conducts a case study in an English-speaking state university located in Central Anatolia, Turkey on the participants, who benefited from the Erasmus+ exchange. The study shows that EU'S educational policy is a major tool in terms of stimulating social learning in candidate countries and preparing them for adaptation and diffusion of European norms and identity.
Keywords: european union; educational policy; exchange programs; norm-building